Bacillus: a eco-friendly source for plant development and sanity (Research, Society and Development, 2022)
Bacillus are non-pathogenic gram-positive bacteria capable of producing resistant spores. They have several beneficial characteristics to crop production, such as increased plant growth, resistance to abiotic/biotic stresses, nutritional improvement, and potential for bioremediation of contaminated soils. The use of microorganisms in agriculture has increased due to the reduction in the use of agrochemicals, and sustainable production. Therefore, the present study was based on bibliographical research on the current state of the art of biotechnological prospecting and obtaining commercial products of Bacillus for the agricultural sector. The search was conducted through the Google Academic platform limiting the search to the years 2015 to 2020. Papers that explained in vitro or in vivo prospecting methodologies of Bacillus with promoter or protective activity of plants and those that described microbial inoculants with this genus were selected. Different species of Bacillus can modulate plant growth producing plant hormones. Molecular biology tools such as DNA sequencing and PCR are applied to the study of genes involved in plant growth modulation by Bacillus such as AcPho, ipdC and asbA. For the elaboration of agricultural bioproducts, vegetative structures or endospores are used, under an optimal concentration of 1 x 108 CFU/mL. In the face of species diversity, many have not yet been studied and are promising to become bioproducts. This fact is enhanced by the immeasurable applicability of Bacillus.